Analisis Penerapan Akuntabilitas PSAK 109, Tata Kelola dan Efektivitas Teknologi pada Laz Ummul Quro Bogor - Riya Dwi Andari; Hurriyaturrohman Hurriyaturrohman; Azolla Degita Azis (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Zakat is one of the requirements in Islamic law that must be fulfilled by every Muslim based on the word of Allah surah At-Taubah 103, which in its meaning zakat is worship that can connect humans with creators or humans with humans Habluminallah and Habluminannas, so in its management, it requires the professionalism of the amil in collecting and distributing ZIS (Zakat, Infaq, Sedekah). The existence of the Lembaga Amil Zakat (LAZ) is intended so that ZIS can be managed and distributed optimally and on target. This study aims to find out how the application of PSAK 109, governance, and effectiveness of the use of technology in entities is very important because LAZ's compliance with regulations can affect LAZ's performance as a ZIS collecting and distributing institution. The research results show that LAZ Ummul Quro Bogor has implemented PSAK 109 in its financial records but is still constrained in determining fair value. In governance, indicators of transparency and responsibility are still experiencing problems and the percentage of effectiveness in using technology at LAZ is still low with a percentage of 60% in the less effective category.